The pentameric chloride channel BEST1 is activated by extracellular GABA - Swati Pant; Stephanie W. Tam; Stephen B. Long (Proceedings of the National Academy of Sciences, 2025)
Bestrophin-1 (BEST1) is a chloride channel expressed in the eye and other tissues of the body. A link between BEST1 and the principal inhibitory neurotransmitter γ -aminobutyric acid (GABA) has been proposed. The most appreciated receptors for extracellular GABA are the GABA B G-protein-coupled receptors and the pentameric GABA A chloride channels, both of which have fundamental roles in the central nervous system. Here, we demonstrate that BEST1 is directly activated by GABA. Through functional studies and atomic-resolution structures of human and chicken BEST1, we identify a GABA binding site on the channel’s extracellular side and determine the mechanism by which GABA binding stabilizes opening of the channel’s central gate. This same gate, “the neck,” is activated by intracellular [Ca 2+ ], indicating that BEST1 is controlled by ligands from both sides of the membrane. The studies demonstrate that BEST1, which shares no structural homology with GABA A receptors, is a GABA-activated chloride channel. The physiological implications of this finding remain to be studied.